3D enabled olfactory, haptic and audio assisted virtual learning framework for visually impaired learners - Chit, Su Mon * (2022)
Visually impaired (VI) people encounter difficulties in their regular activities due to limited vision. Providing them the equal opportunity is crucial, especially in the virtual learning environment (VLE), as limited applications are available. A variety of technology-assisted and non-technology-assisted tools are available for the VI to assist in their daily activities. However, VI learners do not use virtual learning applications due to rich media involvement, which is unsuitable for them. Haptic or sense of touch is one of the technologies useful in VLE for VI learners. It can be used with audio sense and olfactory as additional senses to enhance the learning experience. This research aims to design a learning framework to develop a virtual learning environment for the VI learner. The study aims to investigate the requirements of 3D-enabled olfactory, haptic, and audio-based applications for VI users in a VLE, design a framework to develop an application for the VI in a VLE, and validate the framework by conducting usability testing. The questionnaire for adult VI was adopted from the USE questionnaire, which tests the Usability, Satisfaction as well as Ease of Use, and ease of Learning of the application. Questionnaire for children VI tested the application's effectiveness, operability, efficiency, and satisfaction. Audio is the highest factor in identifying the correct object for VI adults and children. A total of 26 VI participated, and 21 of them are VI adults while 5 are VI children. Based on the usability with VI adults, average ratings are above 5 out of 7, and for the usability testing with VI children, average ratings are 3.7 and above out of 5. Hence, the rating obtained from usability tests were above average. The contributions of the research are (in) the development of a learning framework for the VI in VLE, (ii) a prototype using a learning framework (iii) instruments for testing and evaluation of the framework and the prototype. The research was solely based on the Malaysian context and used only one haptic device. Thus, different haptic devices can be used to compare their effectiveness. The research can also be enhanced in other countries for learners with disabilities such as deaf, blind, and mute learners in learning calligraphybased languages.